2017
DOI: 10.1186/s40557-017-0159-y
|View full text |Cite
|
Sign up to set email alerts
|

Participation inequality in the National General Health Examination based on enterprise size

Abstract: BackgroundHealth examinations are performed so that diseases can be identified and treated earlier. Several studies have evaluated the determinants of participation in health examinations including cancer screening, but few have evaluated the relationship between the size of the enterprise and their participation in Workers’ General Health Examinations (WGHE). The aim of the present study was to estimate the association of WGHE participation with the size of the enterprise and the type of policyholder.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The better the general health screenings, the lower the number of serious diseases that develop, and medical expenses have also been reduced [6,8]. Health screenings are also associated with reductions in cerebral cardiovascular disease and average hospitalization days [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The better the general health screenings, the lower the number of serious diseases that develop, and medical expenses have also been reduced [6,8]. Health screenings are also associated with reductions in cerebral cardiovascular disease and average hospitalization days [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, regular screening may be less accessible to such groups. Indeed, from 2006 to 2013, workers employed by enterprises with < 50 employees were about 50% less likely to participate in general health examinations than were those employed by enterprises with ≥300 employees [40].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the health examination (HE) of workers in 2016, the proportions of suspected general diseases (C2), diagnosed general diseases (D2), suspected occupational diseases (C1), and diagnosed occupational diseases (D1) were 37.0, 34.9, 36.1, and 28.7%, respectively [ 4 ]. In a study on the participation rate of general HE of workers by the size of the business based on the data from the National Health Insurance Corporation from 2006 to 2013, it was found that the participation rate of enterprises with less than 50 non-white-collar workers and 50–299 non-white-collar workers were lower than that of enterprises with more than 300 non-white-collar workers [ 5 ]. Therefore, both health management of EW and quality management of these services are deemed important.…”
Section: Introductionmentioning
confidence: 99%